A Green, Sustainable Diels-Alder Protocol for the Synthesis of Tetrahydro-1H-isoindole-1,3(2H)-dione Catalyzed by Chiral Ionic Liquid. - Dinanath D. Patil,Gurumeet. C. Wadhawa, Vitthal S Shivankar , Pallavi Tiwari Roy,Nandkumar A. Borade, Nitin A. Mirgane (International Journal of Advanced Science and Technology, 2020)
A convenient procedure has been established for the preparation of tetrahydro-1H-isoindole-1,3(2H)-dione (Diel-Alder adduct) using maleimide catalyzed by imidazole based achiral and chiral ionic liquid, under solvent free environments. Achiral and chiral ionic liquids are used as a solvent and a catalyst. Operational simplicity, reusable catalyst, no tedious work up, environment friendly and high yields are some of the key features of the protocol.